Answer:
ln(3) + 5 - 3ln(x) or 6.0986 - 3ln(x)
Explanation:
![ln((3e^(5) )/(x^3) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zd0m8khwfgf9pqx16qf9mwos96ohoyas27.png)
=
, since ln(x/y) = ln(x)-ln(y)
= ln(3) +
, since ln(xy) = ln(x) + ln(y)
= ln(3) +
![ln(e^5)-ln(x^3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3voumresep3huijevzj6x6or07d60ulkpm.png)
=
, since ln(
) = yln(x)
= ln(3) + 5 -3ln(x) , since ln(e)=1
if needed further simplification,
ln(3) = 1.0986
ln(e) = 1
= 6.0986 - 3ln(x)